Current Evidence on the Usefulness of Potential Therapies in the Prevention of COPD Exacerbations: Beyond the Use of Bronchodilator Therapy and Inhaled Corticosteroids - Juan Marco Figueira-Gonçalves; Francisco Javier Callejas-González; Rafael Golpe; Luis Máiz-Carro; Marta Marín-Oto; Javier de Miguel-Díez; Guillermo Samuel Loscertales-Vacas; José María Tordera-Mora; Álvaro Hurtado-Fuentes (Open Respiratory Archives)
Prevention of exacerbations is a key objective in chronic obstructive pulmonary disease (COPD) management. The adverse effects of an exacerbation include a negative impact on patient quality of life and symptoms, an accelerated rate of decline in lung function, hospital admissions, and increased mortality. Clinical guidelines related to COPD management recommend smoking cessation and inhaled therapy (bronchodilators with or without corticosteroids) as the mainstay for these patients. Apart from the above-mentioned treatment, other potential therapies, such as mucolytic agents, antibiotics (oral or inhaled), phosphodiesterase-4 inhibitors or vaccination, are available and have been shown to reduce the incidence of exacerbations. In this brief narrative review, we will examine the efficacy of various treatments for preventing COPD exacerbations, beyond the use of bronchodilator therapy and inhaled corticosteroids. Resumen: La prevención de las exacerbaciones es un objetivo clave en el tratamiento de la enfermedad pulmonar obstructiva crónica (EPOC). Los efectos adversos de una exacerbación incluyen un impacto negativo en la calidad de vida y los síntomas del paciente, un deterioro acelerado de la función pulmonar, un mayor riesgo de ingresos hospitalarios y un aumento de la mortalidad. Las guías de práctica clínica relacionadas con el tratamiento de la EPOC recomiendan el cese tabáquico y la terapia broncodilatadora con o sin corticosteroides inhalados como tratamiento base para estos pacientes. Aparte de los tratamientos mencionados, existen otras terapias potenciales, como son los agentes mucolíticos, los antibióticos (orales o inhalados), los inhibidores de la fosfodiesterasa-4 o la vacunación, entre otros, que han demostrado su papel en la prevención de las agudizaciones. En esta breve revisión narrativa examinaremos la eficacia de estos tratamientos más allá del uso de la terapia broncodilatadora y los corticosteroides inhalados.